Changes in sST2 and NT-proBNP levels predict early cardiac arrhythmia in breast cancer patients treated with anthracycline-containing chemotherapies - Chen, Cuncun; Zheng, Hui; Wang, Yanchun; Tong, Ying; Zhang, Heng; Xie, Suhong; Ma, Xiaolu; Jiang, Minglei; Gong, Zhiyun; Yan, Tianqing; Tian, Yanan; Guo, Lin; et al. (Frontiers in Cardiovascular Medicine, 2024)
BackgroundCardiovascular biomarkers are crucial for monitoring cancer therapy-related cardiac toxicity, but the effects on early stage are still inadequate. To screen biomarkers in patients with breast cancer who receive anthracycline-containing chemotherapy, we studied the behavior of six biomarkers during chemotherapy and their association with chemotherapy-related cardiac toxicity.MethodsIn a prospective cohort of 73 patients treated with anthracycline-containing chemotherapy, soluble suppression of tumorigenicity 2 (sST2), high-sensitivity cardiac troponin T, N-terminal pro-B-type natriuretic peptide (NT-proBNP), myoglobin, creatine kinase isoenzyme MB, and heart-fatty acid binding protein were measured at baseline, during chemotherapy cycle (C1–C6). According to whether arrhythmia occurred, patients were divided into two groups (healthy group or arrhythmias group), and basic clinical characteristics were collected and compared. Logistic regression analyses and receiver operating characteristic (ROC) curves were conducted to investigate the association between the changes in biomarkers and arrhythmia.ResultssST2 levels increased significantly from baseline to C1 (P < 0.01). NT-proBNP levels decreased from baseline to C1 and C5 (P < 0.01). The logistic regression analysis showed a greater risk of arrhythmia was associated with interval changes in sST2 [odds ratio (OR): 1.27; 95% CI: 1.03–1.56; P = 0.024] and NT-proBNP (OR: 0.83; 95% CI: 0.70–0.98; P = 0.029). The ROC curves showed that ΔsST2, ΔNT-proBNP, and ΔsST2 + ΔNT-proBNP had good predictive value for arrhythmia (areas under the curves were 0.631, 0.633, and 0.735, respectively, P < 0.05).ConclusionsEarly changes in sST2 and NT-proBNP levels offer additive information for early arrhythmia prediction in breast cancer patients who receive anthracycline-containing chemotherapy.